Mediating Role of Self-Concept in Perfectionism and Mental Health of Adolescents in the City of Shiraz in 2012 - Maryam Totonchi; Siamak Samani; Keramatallah Zandi Ghashghaei (Fasa University of Medical Sciences, 2012)
Background and Objective: The goal of this study was to describe the mediating role of self-concept in perfectionism and mental health.Materials and Methods: The sample group in this study included 400 high school students (200 boys and 200 girls) from Shiraz with the mean age of 16.37±0.93 for the girls and 16.12±0.63 for the boys. Data were gathered through the application of three scales: Mandaglio and Pyerist Self-concept Scale (P.M.S.P.S) Depression and Anxiety and Stress Scale of Lovibond and Lovibond (DASS-21) and Negative and Positive Perfectionism Scale of Terri-Short et.al. The validity and reliability of these scales were reviewed during this study.   Results: The result of the Path analysis test showed the mediating role of self-concept in perfectionism and mental health. This analysis illustrated that negative and positive perfectionism, both in a direct and indirect way, had a significant role in mental health. The rate of the direct effect of positive perfectionism on mental health was 0.17 (p value ;amplt0.001) and the rate of the indirect variable through self-concept was 0.06 (p value ;amplt0.001). Also, the rate of the direct effect of negative perfectionism on mental health was 0.39 (p value ;amplt0.001) and rate of the indirect effect of this variable on self-concept was 0.01(p value ;amplt0.001).Conclusion: the findings of this study showed that self-concept had a mediating role in mental health and perfectionism. In other words, positive perfectionism of a person has a positive effect on self-concept and, as a result, positive self-concept confers mental health improvement. On the other hand, negative perfectionism leading to a decrease in mental health and an increase in excitement problems of a person.